MARKETING COMPETENCIES OF TRADITIONAL TRADERS IN THE PANORAMA LEMBANG MARKET BANDUNG BARAT DISTRICT - Yanti Purwanti; Nurhayati Nurhayati; Teddy Hikmat Fauzi (Universitas Pasundan, 2021)
The marketing environment is developing very dynamically, has influenced the existence of traditional markets in Indonesia. This rapid and dynamic environmental change, such as the increasing number of modern shops / retails / minimarkets, has an impact on the existence of traditional markets. Traditional markets as a source of economy for the people in Indonesia, which have unique characteristics with bargaining transactions, are also faced with the classic market problems that are identical with smell, muddy, dirty, are demanded to continue to make changes to be able to compete with modern shops. Market revitalization efforts, changes in consumer behavior, as well as market management professionalism need to be improved so that traditional markets can compete with modern shops and have a positive image in society. In this study, it tries to offer a strategy in developing traditional markets, through the concept of marketing within the framework of marketing competence of traditional market traders, especially in Pasar Panorama Lembang, West Bandung Regency. The research method was carried out through survey techniques, by conducting interviews, distributing questionnaires and collecting secondary data through searching journals, documentation and other sources. The questionnaire was distributed to traders using accidental sampling techniques of several types of commodities sold in the market. Based on the results of the research, the competence of Trader Marketing in Panorama Lembang Traditional Market, West Bandung Regency shows that the knowledge, understanding, attitudes, and skills of traders based on product, price, promotion and distribution elements have different competencies based on the types of commodities sold by traders. . Marketing competence of merchants who sell fashion has a level of marketing competence above traders who sell basic food commodities. That includes individual competences of traders such as knowledge, attitudes, skills, understanding and values. The marketing competence of traders in the traditional market Panorama Lembang, West Bandung Regency, does not yet fully know and understand the concept of marketing in their merchandise marketing activities. Marketing competence needs to be given strengthening related to product, price, promotion, and distribution elements to traders to improve the existence of traditional markets that are competitive and adaptive to market changes, towards a market that is safe, clean, comfortable, and continues to be of interest to the public to shop at the market. traditional.